A study of the adoption and implementation of enterprise resource planning (erp): Identification of moderators and mediator - Md. Aftab Uddin; Mohammad Sarwar Alam; Abdullah Al Mamun; Tohid-Uz-Zaman Khan; Ayesha Akter (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Given the dearth of studies in developing and Asian countries' context, the present study attempts to excavate the predictors of enterprise resource planning (ERP) adoption and implementation. Based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model and open innovation literature, an extended model is proposed encompassing mediator and moderator variables. The study follows the deducting reasoning approach with the positivism paradigm. Out of 235 responses, the study used 225 replies collected through a self-administered sampling, and the data were analyzed by using PLS-based structural equation modeling. The study revealed that the hypothesized direct influences are significant except the influence of facilitating conditions on actual use. Likewise, the intention to use mediates the impact of facilitating conditions on the actual use of ERP. However, there is no moderating effect of education and firms' size among the hypothesized influence. The study contributes to advance the previous findings by using an extended UTAUT model and validates results with the rest of the world.
Keywords: 650; actual use of ERP; enterprise resource planning; intention to use ERP; open innovation; UTAUT